The Relationship Between Knowledge and Students' Attitudes About Premarital Sex at the Madina Husada Midwifery Academy 2024 - Nst, Fepri Dayanti (Cattleya Darmaya Fortuna, 2025)
This is to find out how the relationship between knowledge and attitudes of female students about premarital sex at the Madina Husada Midwifery Academy in 2024. This type of research is a study of female students as part of adolescents who have characteristics like teenagers, namely full of curiosity, searching for identity, unstable emotions and need direction, considered to be a group that is independent and responsible. At this time there is rapid growth and development in physical, emotional, cognitive, and social aspects. This period to parents and trying to achieve independence so that they can be accepted and recognized as adults. The purpose of correlation research is a research method carried out to see the relationship between two variables in a situation or group of subjects. This correlation research uses a cross-sectional method research design, namely the cause and effect variables that occur in the research object are measured or collected at the same time. . Researchers took samples by taking 10 people from each level so that the total sample was 40 people. From the calculation results obtained Chi Square value or X2 count = 15.636, while the Chi Square table value with dk = 2 and a confidence level of 5% is 5.991. Because the X2 table value < X2 or 5.991 < 15.636, it can be concluded that there is a significant relationship between knowledge and student attitudes about premarital sex. From the results of this study, student knowledge about premarital sex is included in the category of sufficient knowledge as many as 85 people (53.8%). Student attitudes towards premarital sex who disagree are 105 people (66.5%). is a critical period, namely the time to struggle to break free from dependency.